Análisis Presupuestal de Gestión de Riesgos de Desastres en salud, Lima-Norte - Gonzales Guzmán, Alberto (2021)
To determine the relationship of the budget goals with the physical goals of the Budget Program 068 “Vulnerability Reduction and Disaster Emergency Response” of the Directorate of Integrated Health Networks North Lima (DIRIS North Lima), 2019. Methodology: Quantitative approach; the population was made up of all the items by which the modified initial budget was divided, as a census sample. The hypothetic-deductive method was used and the Wilcoxon test was applied. Results: With a significance level of 5%, a p-value> 0.05 was obtained, therefore, it is stated that in the DIRIS North Lima budget analysis there is no relationship between the execution of the budgeted goals and the physical goals, through which two situations can be established: (a) low budget execution with high execution of physical goals; or (b) high budget execution with low execution of physical goals. Conclusions: The budget goals are not related to the physical goals of DIRIS Lima-Norte.